Legal Basis And Grounds For The Dismissal Of Claims Before The State Administrative Court (a Study of Decision No. 27/Plw/2024/PTUN.SMD) - Dewi Iriani; Dwi Bambang Wisnu Atmaja; Aisah; Dian Puspita Dewi; Maya Indah Purnama Putri (CV. Cognispectra Publishing, 2026)
The dismissal procedure plays a strategic role in maintaining judicial effectiveness, preventing abuse of the right to bring a claim, and ensuring that only cases satisfying the applicable legal requirements proceed to examination and adjudication. This study examines the legal basis governing the dismissal procedure for claims before the State Administrative Court, with reference to Decision No. 27/Plw/2024/PTUN.SMD, and the grounds on which the judges rejected the opposition to the dismissal order. The study employs normative legal research based on a literature review and qualitative analysis. The findings show that the dismissal procedure is principally governed by Article 62(1), in conjunction with Article 62(3), of Law No. 5 of 1986 concerning State Administrative Courts. The assessment of legal standing concerns direct impact, a legitimate legal interest, and the relevance of the legal issue raised. The court rejected the opposition because, first, the claim concerned a dispute that had previously been filed with substantially the same subject matter and parties; and, second, the claim was submitted after the applicable filing period had expired